Preparation of LaPO4 nanowires with high aspect ratio by a facile hydrothermal method and their photoluminescence - Anukorn Phuruangrat (2018)
LaPO 4 nanowires (NWs) measuring 10-15 nm in diameter and up to 4 μm long were prepared by a 200 C and 12 h hydrothermal reaction of LaCl 3 and Na 3 PO 4 ·12H 2 O solution with pH adjusting by 37 % HNO 3 to 1, without using any surfactants or templates. The as-prepared LaPO 4 NWs were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning and transmission electron microscopy, and UV-visible and photoluminescent spectroscopy. In the present research, photonic luminescence and absorbance of LaPO 4 NWs show the maximum emission at 397.60 nm in the violet region and a band gap of 2.87 eV. © 2012 Springer Science+Business Media B.V.